Analisis Biaya dan Waktu dengan Metode Time Cost Trade Off menggunakan Aplikasi Primavera P6 - Muhammad Fahri Faqihhuddin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
In the construction industry, management costs and construction project time are important factors for achieving project success. Cost overruns and time delays can result in significant financial losses for project owners and contractors. Therefore, it is important to adopt an effective approach to construction management to optimize project costs and time. One method for overcoming problems in achieving construction project cost and time targets is the Time Cost Trade Off (TCTO) method. The TCTO method is an approach used in construction project management to achieve a balance between project costs and time. The analysis results show that the FO Krian Development Project, which has a normal duration of 522 days, can be accelerated to 500 days (scenario 1) and 498 days (scenario 2). Direct costs tend to increase due to additional working hours and additional workforce. The alternative used or which is more profitable in completing the project is to use scenario 2, namely additional labor due to a decrease in duration of 24 days from the normal project time and experiencing a decrease in total project costs of IDR 292,008,708.16.